THE ROLE OF CHINA’S DIGITAL SILK ROAD IN SHAPING THE DIGITAL FUTURE OF CENTRAL ASIAN ECONOMIES - Nimatullaev Khondamir Tursunboy ugli; Mavlanov Ibragim Radjabovich (Web of Journals Publishing, 2025)
This article analyzes the evolution and current role of China’s Digital Silk Road in advancing the digital transformation of Central Asian economies. Drawing on recent official data and international research, the study examines the structure, scale, and key sectors of Chinese digital investment in Kazakhstan, Uzbekistan, Kyrgyzstan, Tajikistan, and Turkmenistan. Special attention is paid to the implementation of 5G networks, digital infrastructure, e-government, and smart city projects. The paper discusses both the opportunities associated with technological modernization—such as improved connectivity, economic diversification, and integration into global value chains—and the challenges, including digital dependency, cybersecurity risks, and issues of technological sovereignty. The article concludes with recommendations for balancing the benefits of Chinese investment with the necessity of ensuring digital security, sustainable development, and competitive market environments in Central Asia.
Keywords: Digital Silk Road, Central Asia, China, digitalization, 5G, smart cities, e-government, infrastructure, technological dependency, cybersecurity, Belt and Road Initiative (BRI), digital economy.